2011
DOI: 10.1007/s10614-011-9279-6
|View full text |Cite
|
Sign up to set email alerts
|

Credit market dynamics: a cobweb model

Abstract: Credit market, Price fluctuations, Market interactions, Interest rate dynamics, Nonlinear dynamics, C02, C6, E4,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Therefore, updating the data reported in Casellina et al (2011) and Uberti et al (2013) to the third quarter of 2012 (Figure 1), it turns out that the spread Δρ t = ρ X,t − ρ Z,t between the average fixed rate ρ X,t and the adjustable one ρ Z,t was inversely related to interest rate EURIBOR ι t : this correlation was −0.7882. It also emerges that, over time, a mechanism of switching was put in action among customer preferences between FRMs and ARMs.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Therefore, updating the data reported in Casellina et al (2011) and Uberti et al (2013) to the third quarter of 2012 (Figure 1), it turns out that the spread Δρ t = ρ X,t − ρ Z,t between the average fixed rate ρ X,t and the adjustable one ρ Z,t was inversely related to interest rate EURIBOR ι t : this correlation was −0.7882. It also emerges that, over time, a mechanism of switching was put in action among customer preferences between FRMs and ARMs.…”
Section: Introductionmentioning
confidence: 79%
“…Recently, a meaningful dataset had been arranged by the Bank of Italy on volumes and average interest rates for FRM and ARM on the Italian mortgage market from 1997 : q1 to 2011 : q4. Together with a brief discussion of the phases of the observed dynamics, Uberti et al (2013) showed how the original model Casellina et al (2011) for interdependent markets fitted to data at a good level and, moreover, they pointed out the capability of model to capture the switching mechanism between FRM and ARM markets, that remains significative also in presence of breaks.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations